Problematic usage of the internet among Hungarian elementary school children: a cross-sectional study - Adam Szapary; Gergely Feher; Ildiko Radvanyi; Eva Fejes; Gabor Daniel Nagy; Csaba Jancsak; Lilla Horvath; Zoltan Banko; Gyula Berke; Krisztian Kapus (BMC, 2024)
Abstract Introduction Problematic usage of the internet (PUI) is perhaps one of the most frequently studied phenomena of the 21st century receiving increasing attention in both scientific literature and the media. Despite intensive research there have been relatively few meaningful studies among elementary school students in Hungary and worldwide, who may be considered as a high-risk population with regard to problematic internet use. The aim of our study was to carry out a complex research focusing on the prevalence and risk factors of PUI among elementary school children aged 10-15 years (Grade 5-8). Methods Demographics included were gender, age, place of stay, type of residence, family type, parental education, start of internet use, used devices, daily internet use, purpose of internet use, internet accounts, ways of keeping in touch with friends and sporting activities. PUI was evaluated using the paper-based version of the Potentially Problematic Use of the Internet Questionnaire. Results Overall, 2000 paper-based questionnaires were successfully delivered and the final analysis included 1168 responses (overall response rate 58.4%). Mean age was 12.55 ± 1.24 years. Female gender (OR = 2.760, p = 0,006, CI 95% 0.065 to 0.384), younger age (11-12 years) (OR = 3.812, p < 0.001, 95% CI: 1.747-4.731), early exposure to the internet (OR = 3.466, p = 0.001, 95% CI 1.535-5.446), living in a small village (OR = 1.081, p = 0.002, 95% CI 1.041-1.186) urgency to answer online (OR = 4.677, p < 0.001, 95% CI: 2.714-6.639), decreased frequency of personal contact with friends (OR = 2.897, p = 0.004, 95% CI: 1.037-1.681), spending more than 6 h online (OR = 12.913, p < 0.001, 95% CI: 10.798-14.892), morning and nighttime internet use (OR = 3.846, p < 0.001, CI 95% 1.886-5.810) and never doing any sports (OR = 2.016, p = 0.044, 95% CI: 1.050-3.354) were independently associated with problematic internet use. Conclusions Based on the results of our questionnaire survey more than 10% seemed to be problematic users in our study population, which is a relatively high rate. Early exposure to the internet as well as younger age were strongly related to this phenomenon. Duration of being online as well as daily time interval of internet use are important predisposing factors. Scarcely studied social factors such as being online at the expense of personal relationships and the lack of physical activity should be payed more attention to prevent the development of PUI.